Thrombopoietin receptor agonists in pharmacotherapy of pediatric immune thrombocytopenia - Olga S. Levchenkova; Viktoriya V. Vorobieva; Vasiliy E. Novikov; Tatiana I. Legonkova; Elena N. Volkova (Belgorod National Research University, 2023)
Introduction: Thrombopoietin receptor agonists are commonly second-line drugs in immune thrombocytopenia (ITP) pharmacotherapy in children and prescribed for chronic ITP refractory to first-line therapy. Standard ITP pharmacotherapy in children: includes prescribing glucocorticoids or intravenous immunoglobulins. Thrombopoietin receptor agonists: Currently Romiplostim and Eltrombopag are used in the Russian Federation pediatrics. Their pharmacodynamic features in comparison with other drugs used in ITP are presented in the paper. Increased thrombocytopoiesis is the dominant, but not the only component of Romiplostim and Eltrombopag mechanism of action. It is relevant to study their effect on immune tolerance in ITP, which may be associated with a persistent platelet response in some patients after drug discontinuation. Conclusion: The issue of thrombopoietin receptor agonist efficacy and safety as well as the mode of their use in ITP children treatment continues to be studied. The high cost of drugs continues to be a limiting factor to their earlier prescription. Generic drugs - Romiplostim and Eltrombopag partly solve the problem, promote their earlier prescription in ITP, but require additional study of their bioequivalence and therapeutic equivalence in comparison with the original drugs.